Economic evaluation of a hybrid renewable energy system (HRES) using hybrid optimization model for electric renewable (HOMER) software—a case study of rural India. (18th February 2021) - Sharma, Kamal Kant; Gupta, Akhil; Kumar, Raman; Chohan, Jasgurpreet Singh; Sharma, Shubham; Singh, J; Khalilpoor, Nima; Issakhov, Alibek; Chattopadhyaya, Somnath; Dwivedi, Shashi Prakash
Abstract: This paper unveils a sustainable energy plan for optimal utilization of available electrical energy resources for an energy-deficient village. The chosen village is Nangal, near Barnala, Punjab, India. Primarily, the requirements of electric energy are recorded and elaborated for around 450 households. Aiming this, the potential to harness electric power and its effective utilization has been identified from the available resources of energy: biomass, agriculture waste and solar photovoltaic (PV) technology. In order to achieve this, a hybrid renewable energy system (HRES) model is proposed whose performance is evaluated by implementing it in hybrid optimization model for electric renewable (HOMER) software. HOMER software provides optimal solution for a commercial biogas plant for catering cooking gas demand. Also, a coordinated solution for solar PV-operated water pumps used for irrigation, village water supply and solar PV street lights is presented and analyzed. In this way, the accurateness of proposed model is investigated by estimating the optimal electric power demand and its economic benefits. It has been revealed that the computed cost of energy and total net present cost are 0.032/KWh and 76, 837, respectively, by the parametric assessment of proposed HRES system. It is envisaged that the proposed model can be a road map for future research engineers in designing an effective energy utilization for villages.